Minutes of the Eighteenth Regular Meeting of the Rocky Mountain Coal Mining Institute held at Denver, Colorado February 13, 14 and 15,1924 (Rocky Mountain Coal Mining Institute, 1924)
The meeting was called to order with President George B. Pryde in the chair, and C. M. Schloss, acting Secrcetary. The meeting immediately pro¬ceeded to the reading of the papers. Mr. L. S. Ickis read a paper by A. L. Jones, entitled, "Underground Sub-Station Control," and elaborating on the general topic of automatic sub-stations. The discussion was led in part by Mr. E. H. Weitzel, acting as Chairman, in Mr. Pryde's temporary absence. Mr. S. R. DeBoer, who specializes on landscape architecture, gave an interesting talk on the subject of "City Planning and Landscape Architecture for Western Coal Camps." Notes were taken of this talk, which will be found in the proceedings. Mr. Pryde then resumed the Chair; There was no discussion of this paper. Mr. Thomas Foster, of Reliance, Wyoming, then read his paper on "Coal Dust in Mines." After the discussion of Mr. Foster's paper, the discussion of Mr. McKeehan's paper on track bonding, read at the Salt Lake meeting, was resumed, and this discussion will be found printed separately in the proceedings. Mr. Schloss then read an amusing and friendly telegram from C. H. Stevenson, of Price, Utah, which caused considerable merriment, and the Chairman asked Messrs. Weitzel, Littlejohn and Schloss to form an appro¬priate answer, and they answered it in the same spirit. The Chairman then announced the banquet for Wednesday evening and the Theatre Party for Thursday evening. The meeting then adjourned. The meeting resumed at 10:15 A. M., Thursday, February 14, 1924. The Chairman announced a photograph of the meeting to be taken at noon, on the Post Office steps, after which the Chairman appointed a nom¬inating committee, consisting of George A. Murphy, F. W. Whiteside and